2018
DOI: 10.3389/fnhum.2018.00209
|View full text |Cite
|
Sign up to set email alerts
|

Structural Gray Matter Changes in the Hippocampus and the Primary Motor Cortex on An-Hour-to-One- Day Scale Can Predict Arm-Reaching Performance Improvement

Abstract: Recent studies have revealed rapid (e.g., hours to days) training-induced cortical structural changes using magnetic resonance imaging (MRI). Currently, there is great interest in studying how such a rapid brain structural change affects behavioral improvement. Structural reorganization contributes to memory or enhanced information processing in the brain and may increase its capability of skill learning. If the gray matter (GM) is capable of such rapid structural reorganization upon training, the extent of vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 59 publications
1
9
0
1
Order By: Relevance
“…We chose to focus specifically on a procedural memory task because the importance of sleep in procedural memory consolidation is well established 16,17 . Furthermore procedural memory task improvements 18 and the associated structural changes 19 have been shown to persist over time, with the same being true for the TMR effects 11 . Our participants were trained on two motor sequences in a Serial Reaction Time Task (SRTT).…”
Section: Introductionmentioning
confidence: 78%
“…We chose to focus specifically on a procedural memory task because the importance of sleep in procedural memory consolidation is well established 16,17 . Furthermore procedural memory task improvements 18 and the associated structural changes 19 have been shown to persist over time, with the same being true for the TMR effects 11 . Our participants were trained on two motor sequences in a Serial Reaction Time Task (SRTT).…”
Section: Introductionmentioning
confidence: 78%
“…This is in keeping with the role of the EC as the interface between the hippocampus and cortex, with the latter sharing limited direct connections (Burman, 2019; Maller et al, 2019). Contemporaneous volumetric increases have been observed in the sensorimotor cortex and the hippocampus during 5 days of visuo-motor training (Kodama et al, 2018), but this is the first evidence of an M1-EC-hippocampal circuit active during motor learning and underlines the potential versatility of quantitative MRI markers in mapping skill acquisition and recovery over time.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast to the initial changes in functional activity, the change in GMV did not occur rapidly (between TP0 and TP1), but was more prolonged in time, with the peak at the end of the PJM course. A number of studies have shown that GMV changes can be detected as early as within a few days or even hours of training as a result of improving, for example, visuomotor skills (e.g., Driemeyer et al, 2008; Kodama, Ono, Yamashita, Ebata, & Liu, 2018; Landi, Baguear, & Della鈥怣aggiore, 2011) or learning new colors (Kwok et al, 2011). We extend these findings by showing that cognitively demanding and time鈥恈onsuming L2 acquisition also results in GMV increases after just a few months of learning.…”
Section: Discussionmentioning
confidence: 99%